Rebecca Riger Tsurumi. The Closed Hand: Images of the Japanese in Modern Peruvian Literature. West Lafayette, Indiana: Purdue UP, 2012. xv + 314 pp. - Miguel Gonzalez-Abellas (Studies in 20th & 21st Century Literature, 2015)
Review of Rebecca Riger Tsurumi. The Closed Hand: Images of the Japanese in Modern Peruvian Literature. West Lafayette, Indiana: Purdue UP, 2012. xv + 314 pp.
Keywords: Book review; Japanese culture; Peruvian literature